Students’ meaning-making processes in an IPE programme with students from education-, health-, and social care programmes. A qualitative study - Braathen, Kaja; Gulbrandsen, Liv Mette (Frontiers in Education, 2023)
Interprofessional collaboration (IPC) is increasingly being recognised as an important mechanism to improve the quality of services offered to children. This study imparts results from an investigation of undergraduate students’ participation in an interprofessional education (IPE) programme focusing on working with children (0-18). The programme participants include students across the disciplines of education, health, and social care. In the study the students’ accounts of group processes by which they negotiated their positions and the relevance of their emerging professional knowledge in interprofessional student groups are explored. The more overarching aim is to contribute to a knowledge base serving the development of broad IPE initiatives. Qualitative interviews were conducted with students (n =15) to explore their experiences participating in the programme. Positioning theory was used as an analytical framework. The results indicate that the students’ joint constructions of the aim of the learning activity were vital for their joint meaning-making in the interprofessional learning (IPL) - groups and for processes of positioning. In addition, students’ participation in the IPL groups was closely linked to their approach to negotiations of relevance. The pedagogical implications of these results are discussed.